Graph analytics for task management - Kor, Yong Wee (Nanyang Technological University, 2020)
This final year project explores the usage of Graph Analytics for Tasks Management. In the area of graph theory in mathematics, signed graphs are special graphs whereby the edges are either labelled as positive or negative. If the product of the weights of each edge in a cycle produces a positive result, that said signed graph is considered balanced. Therefore, it has the capability to simulate real-life scenarios as visual and structural models that otherwise can be difficult to achieve using traditional ways such as performance-based indicators. There are new tools that are available in the market now and development of graph analysis has also taken a leap forward. The purpose of this project is to develop a system which can analyse an organisational structure based on the notion of structural balanced of the signed graph. The system incorporates graphing techniques and trust-based calculations to establish the optimal output for the user.